Aspects of Crop and Physiology of Feijoa (Acca sellowiana [Berg] Burret). A Review (2020)
Feijoa is a fruit tree with great potential for human consumption, cultivated between 1,800 and 2,700 m.a.s.l. in Colombia. It is well adapted to cold temperatures, resisting temperatures <0 °C for a short time, while temperatures >32 °C affect its flowering. It has base temperatures for its state from flower bud to anthesis with 2.89 °C, from anthesis to fruit set with 3.04 °C and from fruit set to harvest 1.76 °C. The tree thrives well in in alluvial soils, deep and rich in organic matter ones. In the tree pruning, the cone formation with three levels of horizontal bent branches and the elimination of suckers are important, thus promoting flowering and longevity of the tree. In the few physiological studies, a low photosynthetic rate (on average between 4 and 6 μmol CO2 m-2 s-1) was found, with high energy demand during flowering, while the transpiration rate of the crown increases with irradiance, temperature and the decrease in relative humidity, showing a greater number of leaf stomata in the upper layer of the crown (91/mm2), compared to the lower layer (78/mm2). The beginning of the reproductive stage is favored by dry conditions, as well as potassium fertilization with 0.5% KH2PO4. In Colombia, fruits of greater caliber and higher productions are achieved through cross-pollination by blackbirds (Turdus fuscater). The fruit needs about 120 to 150 days to develop and there are productions between 30 and 40 kg/tree (≥20 t ha-1). The green color of the fruit in all its stages makes it difficult to determine its maturity state.